2004
DOI: 10.1080/02786820490437505
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of the UVAPS in Measuring Biological Aerosols: Fluorescence Spectra from NAD(P)H Coenzymes and Riboflavin

Abstract: This article presents the results of the performance evaluation of the Ultraviolet Aerodynamic Particle Sizer (UVAPS, model 3312, TSI Inc., St. Paul, MN, USA), the novel instrument for real-time monitoring of biological aerosols. The main objective of the study was to compare the UVAPS response in measuring aerosols containing NADH, NADPH, or riboflavin particles. At the excitation and emission wavelengths at which the UVAPS operates, these compounds are the primary intrinsic fluorophores specific to biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 32 publications
(47 reference statements)
4
40
1
Order By: Relevance
“…The results presented here and from other studies using WIBS instruments, in contrast to reports using other UV-LIF instruments, suggest that the WIBS-4A is highly sensitive to the detection of bacteria using 280 nm excitation (only FL1 emission), but less so using the 370 nm excitation (FL3 emission) (e.g., Perring et al, 2015;Hernandez et al, 2016). A study by Agranovski et al (2003) also demonstrated that the UV-APS was limited in its ability to detect endospores (reproductive bacterial cells from sporeforming species with little or no metabolic activity and thus low NAD(P)H concentration). The lack of FL3 emission observed from bacteria in the WIBS may also suggest a weaker excitation intensity in Xe2 with respect to Xe1, manifesting in lower overall FL3 emission intensity (Könemann et al, 2017).…”
Section: Broad Separation Of Particle Typescontrasting
confidence: 54%
See 3 more Smart Citations
“…The results presented here and from other studies using WIBS instruments, in contrast to reports using other UV-LIF instruments, suggest that the WIBS-4A is highly sensitive to the detection of bacteria using 280 nm excitation (only FL1 emission), but less so using the 370 nm excitation (FL3 emission) (e.g., Perring et al, 2015;Hernandez et al, 2016). A study by Agranovski et al (2003) also demonstrated that the UV-APS was limited in its ability to detect endospores (reproductive bacterial cells from sporeforming species with little or no metabolic activity and thus low NAD(P)H concentration). The lack of FL3 emission observed from bacteria in the WIBS may also suggest a weaker excitation intensity in Xe2 with respect to Xe1, manifesting in lower overall FL3 emission intensity (Könemann et al, 2017).…”
Section: Broad Separation Of Particle Typescontrasting
confidence: 54%
“…The FL3 channel in the WIBS-4A has an excitation of 370 nm and emission band of 420-650 nm, similar to that of the UV-APS with an excitation of 355 nm and emission band of 420-575 nm. Previous studies have suggested that viable microorganisms (i.e., bacteria) show fluorescence characteristics in the UV-APS due to the excitation source of 355 nm that was originally designed to excite NAD(P)H and riboflavin molecules present in actively metabolizing organisms (Agranovski et al, 2004;Hairston et al, 1997;Ho et al, 1999;Pöhlker et al, 2012). Previous studies with the UV-APS and other UV-LIF instruments using approximately similar excitation wavelengths have shown a strong sensitivity to the detection of "viable" bacteria Pan et al, 1999;Hairston et al, 1997;Brosseau et al, 2000).…”
Section: Broad Separation Of Particle Typesmentioning
confidence: 99%
See 2 more Smart Citations
“…As the result, a number of techniques for nearly real-time continuous detection and quantification of biological airborne particles have been developed, including ultraviolet aerodynamic particle sizer spectrometer (UVAPS), bioaerosol mass spectrometer (BAMS), ATP bioluminescence-based method and NanoPCR technique (Agranovski et al 2004c;Russell et al 2005;Xu and Yao 2013;Park et al 2014).…”
Section: Introductionmentioning
confidence: 99%